1990
DOI: 10.1093/carcin/11.11.2005
|View full text |Cite
|
Sign up to set email alerts
|

Strand scission in DNA by quercetin and Cu(II): identification of free radical intermediates and biological consequences of scission

Abstract: Quercetin was shown to reduce oxygen to superoxide. In the presence of Cu(II), the hydroxyl radical was formed. The strand scission of DNA was shown to occur under conditions in which Cu(II), quercetin and either hydrogen peroxide or oxygen were present and superoxide was not a necessary intermediate. Strand scission involved the hydroxyl radical and a radical DNA intermediate. The strand scission reaction was shown to account for the biological activity of quercetin as assayed by bacteriophage inactivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 0 publications
3
17
0
Order By: Relevance
“…Quercetin is a potent mutagen widespread in nature but at its highest levels in bracken fern (Bjieldanes and Chang, 1977;Nakayasu et al, 1986). It causes oxidative DNA damage (Yamashita and Kawanishi, 2000), single-strand DNA breaks (Fazal et al, 1990), DNA rearrangements (Suzuki et al, 1991) and chromosomal aberrations (Ishidate et al, 1988). Additionally, quercetin interferes with several kinases (Jackson and Campo, 1995;Davies et al, 2000).…”
Section: Kip1mentioning
confidence: 99%
“…Quercetin is a potent mutagen widespread in nature but at its highest levels in bracken fern (Bjieldanes and Chang, 1977;Nakayasu et al, 1986). It causes oxidative DNA damage (Yamashita and Kawanishi, 2000), single-strand DNA breaks (Fazal et al, 1990), DNA rearrangements (Suzuki et al, 1991) and chromosomal aberrations (Ishidate et al, 1988). Additionally, quercetin interferes with several kinases (Jackson and Campo, 1995;Davies et al, 2000).…”
Section: Kip1mentioning
confidence: 99%
“…In addition, the mechanism of action of several anti-tumor antibiotics such as bleomycin and adriamycin [23,24] is considered to involve the generation of ROS. Several known antioxidants of plant origin such as flavonoids, generate ROS in the presence of transition metal ions such as copper, and lead to DNA cleavage [12,15,25]. A number of molecules present in human extracellular fluids are considered to have antioxidant function and these include ascorbic acid and uric acid.…”
Section: Discussionmentioning
confidence: 99%
“…The assay involves incorporation of salicylate as a reporter molecule [14]. In earlier reports we have shown that this assay genuinely measures hydroxyl radical production as the production is inhibited by thiourea, benzoate and mannitol [15].…”
Section: Production Of Hydroxyl Radicals" By L-dopamentioning
confidence: 99%
“…The¯a vonoid quercetin is perhaps the best characterised of the fern mutagents. It has been shown that quercetin induces mutations in both prokaryotic and eukaryotic cells (Bjieldanes and Chang, 1977;Nakayasu et al, 1986), through the generation of DNA single-strand breaks (Rahaman et al, 1990;Fazal et al, 1990) and that it can substitute for DMBA in a two-stage cell transformation model (Sakai et al, 1990). In addition to its mutagenic properties, quercetin induces cell cycle arrest (Hosokawa et al, 1990;Ranelletti et al, 1992;Plaumann et al, 1996), disrupts normal cellular signalling pathways by interfering with kinases and phosphatases (Graziani et al, 1983;Van Wart-Hood et al, 1989;Matter et al, 1992) and induces protein degradation (Ahmed et al, 1994).…”
Section: Introductionmentioning
confidence: 99%